Novel actuation design of a gait trainer with shadow leg approach - Meuleman, Jos; van Asseldonk, Edwin H. F.; van der Kooij, Herman (2013 IEEE 13th International Conference on Rehabilitation Robotics (ICORR), 2013)
Robotic gait training has developed since the end of the 20 th century, yet there is much room for improvement in the design of the robots. With the conventional exoskeleton structures, donning of patients in a gait trainer usually is a cumbersome process due to the need of joint alignments and normal walking is often hindered due to obstructed arm swing. Our goal was to design a gait training robots that overcomes these limitations. We propose a novel design in which these drawbacks are reduced to a great amount. By using a parallel structure behind the patient (shadow leg) that is connected to the patient joints with rods, little alignment is needed, the area lateral to the hip is left free, and thus arm swing is not obstructed. The construction is lightweight, because the actuators are mounted on a fixed base and the transmission of power is executed with light weight rods. An end stop in the shadow leg prevents hyper extension of the patient's knee. The relationship between motor displacement and human joint rotations is nonlinear. In this paper we derive the nonlinear relationships between motors and patient joints and verify these. calculations with a measurement. The device has been built, now tests with subjects are required to assess if subjects can indeed walk normally in the robot.